Estimativa de taxas de denudação mecânica da bacia hidrográfica do Rio Quatorze (PR) pela análise de sólidos em suspensão - Aguiar, Wagner de (2012)
The object of this paper is to estimate the mechanical denudation rates for the river basin Quatorze in the sectors of the upper valley and the mouth of the river. The basin is located in the municipality of Francisco Beltrão, in Paraná, draining the left bank of the middle valley of the river basin Marrecas. Monitoring the field began in august 2011, rising daily data of rainfall, flow and concentration of suspended solids in the sections of the channels drained the upper valley and the mouth of the river, to obtain the discharges suspended solids. Carrying out further surveys in ten soil profiles distributed throughout the basin, allowing the identification of the main soil classes (Regolithic Entisols, Inceptisols, Oxisols and Nitossolos) and the measurement of laboratory parameters such as density and real, total porosity and fines content (silt and clay). In the monitored period was recorded daily rainfall, which occurred on august 19, 165 mm, resulting in large peak flows and discharge of suspended solids, contributing to the total rainfall for the month of august 2011, 343 mm, reached the highest monthly index for the month of august, the last 37 years, according to data provided by the Meteorological Station of Francisco Beltrão. Recognizing that the largest fraction pedological removed by the force of runoff is composed of mud (silt and clay), this parameter was quantified for soils of the basin, yielding an average of 91.87%. From the data of total suspended solid discharge (1,616.54 tons. in the upper valley and 5960.38 tons. at the mouth) and the average density (1.05 g.cm-³) of soil profiles were estimated denudation rates for the month of august 2011, 0.0419 mm in the sector of the basin drained by the upper valley and 0.0527 mm in the area drained by the mouth of the river. These results were extrapolated to annual estimates, based on the monitored period of rainfall and monthly average of the years 1974 to 2010. The standard deviations of the average monthly rainfall, for those years, enabled the establishment of maximum and minimum estimates for the annual rates of denudation. The sector of the upper valley had average estimate of 0.2458 mm.yr-¹ can vary over a range of 0.1069 mm.yr-¹ to 0.3848 mm.yr-¹, while the sector had the mouth of the river estimated annual average higher, 0.3092 mm.yr-¹ may, however, vary in a range of 0.1344 mm.yr-¹ to 0.4840 mm.yr-¹.